2007
DOI: 10.1152/ajpheart.01065.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate receptor expression in cardiac fibroblasts is modulated by in vitro culture conditions

Abstract: Landeen LK, Aroonsakool N, Haga JH, Hu BS, Giles WR. Sphingosine-1-phosphate receptor expression in cardiac fibroblasts is modulated by in vitro culture conditions. Am J Physiol Heart Circ Physiol 292: H2698 -H2711, 2007. First published March 2, 2007; doi:10.1152/ajpheart.01065.2006.-The bioactive molecule sphingosine-1-phosphate (S1P) binds with high affinity to five recognized receptors (S1P1-5) to affect various tissues, including cellular responses of cardiac fibroblasts (CFbs) and myocytes. CFbs are ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
(77 reference statements)
1
21
0
Order By: Relevance
“…Conversely, binding of these growth factors to their RTKs can also translocate and activate SphK1 (Pitson et al, 2005), leading to spatially restricted formation of S1P that in turn further activates inside-out signaling . Additionally, some of these RTKs, such as PDGF receptor, can also increase S1P 1 mRNA expression (Landeen et al, 2007), leading to further complex interplay between S1P receptors and RTKs. S1P 2 , like S1P 1 and S1P 3 receptors, is also widely expressed and is the dominant receptor in the vascular smooth muscle cells (Waeber et al, 2004).…”
Section: Sphingosine 1-phosphate Receptorsmentioning
confidence: 99%
“…Conversely, binding of these growth factors to their RTKs can also translocate and activate SphK1 (Pitson et al, 2005), leading to spatially restricted formation of S1P that in turn further activates inside-out signaling . Additionally, some of these RTKs, such as PDGF receptor, can also increase S1P 1 mRNA expression (Landeen et al, 2007), leading to further complex interplay between S1P receptors and RTKs. S1P 2 , like S1P 1 and S1P 3 receptors, is also widely expressed and is the dominant receptor in the vascular smooth muscle cells (Waeber et al, 2004).…”
Section: Sphingosine 1-phosphate Receptorsmentioning
confidence: 99%
“…Cardiac fibroblasts make up >50% of the total heart cells and provide a pivotal contribution to cardiac remodeling (80-82). It has been shown that cardiac fibroblasts express S1P1-3 receptors and that the levels of these receptors in cultured cardiac fibroblasts are significantly altered after stimulation by the factors associated with remodeling such as transforming growth factor (TGF)-β1, TNF-α, and platelet-derived growth factor (83). Furthermore, in cultured cardiac fibroblasts, TGF-β stimulates S1P production via SPHK1 and that S1P increases collagen expression via S1P2 receptor; TGF-β-stimulated collagen production is blocked by the inhibition of SPHK1 or S1P2, demonstrating that S1P is a critical mediator in TGF-β-induced fibrogenic effect in cardiac fibroblasts (84).…”
Section: S1p Signaling In Heartmentioning
confidence: 99%
“…16 Although S1P1 receptors predominate in cardiac myocytes, S1P3 receptors are the most prevalent subtype in cardiac fibroblasts. 21 Activation of S1P receptors on fibroblasts can mediate migration and proliferation, responses that are necessary for fibrosis and critical to cardiac remodeling. For instance, adult cardiac fibroblast migration in response to growth factors is reduced by S1P3 receptor deletion.…”
Section: Effects On the Failing Heartmentioning
confidence: 99%